Structural engineering of stabilized, expanded epitope nanoparticle vaccines for HPV - Helble, Michaela; Zhu, Xizhou; Bhojnagarwala, Pratik S.; Liaw, Kevin; Gao, Yangcheng; Kim, Amber; Bayruns, Kelly; McCanna, Madison E.; Park, Joyce; Konrath, Kylie M.; Garfinkle, Sam; Brysgel, Taylor; et al. (Frontiers in Immunology, 2025)
Oncogenic forms of HPV account for 4.5% of the global cancer burden worldwide. This includes cervical, vaginal, vulvar, penile, and anal cancers, as well as head and neck cancers. As such, there is an urgent need to develop effective therapeutic vaccines to drive the immune system’s cellular response against cancer cells. One of the primary goals of cancer vaccination is to increase the potency and diversity of anti-tumor T-cell responses; one strategy to do so involves the delivery of full-length cancer antigens scaffolded onto DNA-launched nanoparticles to improve T-cell priming. We developed a platform, making use of structural prediction algorithms such as AlphaFold2, to design stabilized, more full-length antigens of relevant HPV proteins and then display them on nanoparticles. We demonstrated that many such designs for both the HPV16 E6 and E7 antigens assembled and drove strong CD8+ T-cell responses in mice. We further tested nanoparticles in a genetically diverse, more translationally relevant CD-1 mouse model and demonstrated that both E6 and E7 nanoparticle designs drove a CD8+ biased T-cell response. These findings serve as a proof-of-concept study for nanoparticle antigen design as well as identify new vaccine candidates for HPV-associated cancers.